PERANCANGAN APLIKASI ANDROID PEMBUATAN GAME TEBAK GAMBAR KOMPONEN-KOMPONEN KOMPUTER - Gumri Kesuma; Fithry Tahel (Himpunan Penggiat Teknologi Informasi Abrar Indonesia, 2023)
Games are entertainment that everyone likes, both children, adults and parents. Apart from using games to lighten activities, it can also train the mind to find solutions to solving problems in games. In the past, games such as card games, chess, snakes and ladders, hide and seek and others were played traditionally. With the development of technology, the game has developed into a more modern technology. Now there are many new games that use modern technology in their production and use, technological developments can also be used in obtaining information and adding insight through the use of mobile gadgets, while a computer is a collection of several components that have functions that are interconnected to carry out a computer, but even though many people know computers, there are still many people who don't know what computer components are, therefore to introduce what computer components are, the effort used is to utilize multimedia technology, one of which is a game .